Glycine increased ferroptosis via SAM-mediated GPX4 promoter methylation in rheumatoid arthritis. (8th February 2022) - Ling, Hanzhi; Li, Man; Yang, Chenglin; Sun, Siyuan; Zhang, Wei; Zhao, Lin; Xu, Nannan; Zhang, Jinhao; Shen, Yecheng; Zhang, Xu; Liu, Can; Lu, Liangjing; et al.
Abstract: Objective: Over-proliferation of synovium is a key event of invasive pannus formation and cartilage damage in the progression of RA disease. At the same time, ferroptosis may play a pivotal role in maintaining the balance of proliferation and death of synovium. In this study, we firstly evaluated the ferroptosis level in RA fibroblast-like synoviocytes (FLS) and then explored the role of glycine in ferroptosis. Methods: Ferroptosis was evaluated in RA synovium and FLS. The therapeutic effect of glycine on RA was evaluated by clinical and histopathological score and cytokine level in a CIA mouse model. The influence of glycine on ferroptosis was evaluated by mitochondrial morphology observation and membrane potential assay in RA FLS. Methylase expression was detected to explore the mechanism behind the effect of glycine on glutathione peroxidase 4 (GPX4) methylation. Results: Compared with healthy controls, ferroptosis decreased in the RA synovium and FLS, with a decrease in Acyl Coenzyme A Synthetase Long Chain 4 (ACSL4) and an increase in Ferritin heavy chain 1 (FTH1), GPX4 and cystine/glutamate antiporter solute carrier family 7 member 11 (SLC7A11). Although both oxidation and antioxidation levels of lipids were higher in RA FLS than in healthy controls, the increase in antioxidation was slightly higher than oxidation. RNA-seq and verification showed that glycine regulated the ferroptosis pathway through increase S-adenosylmethionine (SAM) concentration and decrease the expression of GPX4 and FTH1 by promoting SAM-mediated GPX4 promoter methylation and reducing FTH1 expression in RA FLS. Conclusions: In summary, we confirmed a decline in ferroptosis in RA and explored that glycine enhanced ferroptosis via SAM-mediated GPX4 promoter methylation and ferritin decrease. Graphical Abstract: